2008
DOI: 10.1007/s11664-008-0566-5
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Growth Pits in Lead Salt Epilayers Grown by Molecular Beam Epitaxy

Abstract: We present a detailed study on the surface morphologies and chemical composition of growth pits in lead selenide (PbSe) epilayers grown by molecular-beam epitaxy. Various growth pits were investigated by scanning electron microscopy and energy-dispersive x-ray analysis. The vast majority of growth pits within the PbSe epilayers contained either single or multiple PbSe microcrystals with a distinct cuboid shape. Based on the observed structures and morphologies of the PbSe microcrystals, the formation mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…[17] Lead salt semiconductors have a distinct nature of self-crystallization -nucleation/formation of high quality micro-size monocrystalline materials without transferring the mismatch information from the substrate. Such self-crystallized single crystals were also found in lead salt epitaxial films, which were previously portrait as growth pits [18] as is shown in figure 3. Transmission electron microscopy (TEM) study shows that these self-crystallized cuboids have very high crystal quality with no dislocation observed, as shown in figure 4.…”
Section: High Quality One Dimensional Pbse Microcrystals For Photovolsupporting
confidence: 59%
“…[17] Lead salt semiconductors have a distinct nature of self-crystallization -nucleation/formation of high quality micro-size monocrystalline materials without transferring the mismatch information from the substrate. Such self-crystallized single crystals were also found in lead salt epitaxial films, which were previously portrait as growth pits [18] as is shown in figure 3. Transmission electron microscopy (TEM) study shows that these self-crystallized cuboids have very high crystal quality with no dislocation observed, as shown in figure 4.…”
Section: High Quality One Dimensional Pbse Microcrystals For Photovolsupporting
confidence: 59%
“…There have been studies on the threading dislocations in IV-VI semiconductors [4,5]. The growth pits in the IV-VI semiconductors, however, have not been intensively studied until recently by our research group [6]. We found that the majority of growth pits within the PbSe epilayers contain either single or multiple PbSe micro-crystals with a distinct cuboid shape.…”
Section: Introductionmentioning
confidence: 77%
“…A few large cuboid growth pits of various shapes and a number of smaller defects, ranging from less than one-half to several micrometres in size are present. The plan-view SEM image, figure 1(b), shows that the large growth pits are composed of multiple-faceted features with cubic symmetry and have been named 'PbSe cuboids' [9]. These cuboids are typically found as single cubes, but also form larger conglomerates of multiple cubes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, much effort has been devoted to improving material quality and understanding the formation of dislocations and other growth defects in IV-VI materials [7][8][9]. It was found that one prevalent type of growth defect in molecular beam epitaxy (MBE) grown PbSe epitaxial layers, the so-called 'cuboid growth pits', was composed of single or multiple micrometre-sized PbSe crystals with their geometric structures embedded in the PbSe (1 1 1) epilayers [9]. For the prevailing II-VI and III-V materials such as Hg 1−x Cd x Te and In 1−x Ga x As, the formation of various growth defects such as twins, craters, hillocks and V-shaped defects has been intensively studied and different models have been proposed to explain the growth mechanisms [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation